Multiple independent inputs are required for activation of the p70 S6 kinase. - Weng, Q P (1995)
Previous studies have shown that the noncatalytic carboxy-terminal tail of the p70 S6 kinase (amino acids 422 to 525) contains an autoinhibitory pseudosubstrate domain that is phosphorylated in situ during activation and in vitro by mitogen-activated protein kinases. The present study shows that a recombinant p70 deleted of the carboxy-terminal tail (p70 delta CT104) nevertheless exhibits a basal and serum-stimulated 40S kinase activity and susceptibility to inhibition by wortmannin very similar to those of the parent, full-length p70 kinase. Carboxy-terminal deletion reduces the extent of maximal inhibition produced by rapamycin, from > 95% in the full-length p70 to 60 to 80% in p70 delta CT104, without altering the sensitivity to rapamycin inhibition (50% inhibitory concentration of 2 nM). Serum activation of p70 delta CT104, as with the parent, full-length p70, is accompanied by an increase in 32P content (about twofold) in situ and a slowing in electrophoretic mobility; both modifications are inhibited by pretreatment with wortmannin or rapamycin. 32P-peptide maps of p70 delta CT104 show multisite phosphorylation, and wortmannin and rapamycin appear to cause preferential dephosphorylation of the same subset of sites. Thus, it is likely that activation of the kinase requires phosphorylation of p70 at sites in addition to those previously identified in the carboxy-terminal tail. Evidence that the carboxy-terminal tail actually functions as a potent intramolecular inhibitor of kinase activity in situ is uncovered by deletion of a short acidic segment (amino acids 29 to 46) from the p70 amino-terminal noncatalytic region. Deletion of amino acids 29 to 46 causes a >95% inhibition of p70 activity despite continue phosphorylation of the carboxy-terminal tail in situ; additional deletion of the carboxy-terminal tail (yielding p70 delta 29-46/ delta CT104) increases activity 10-fold, to a level approaching that of p70 delta CT104. Deletion of residues 29 to 46 also abolishes completely the sensitivity of p70 to inhibition by rapamycin but does not alter the susceptibility to activation by serum of inhibition by wortmannin. Although the mechanisms underlying the effects of the delta 29-46 deletion are not known, they are not attributable to loss of the major in situ p70 phosphorylation site at Ser-40. Thus, activation of the p70 S6 kinase involves multiple, independent inputs directed at different domains of the p70 polypeptide. Disinhibition from the carboxy-terminal tail requires, in addition to its multisite phosphorylation, an activating input dependent on the presence of amino acids 29 to 46; this p70-activating input may be the same as that inhibited by rapamycin but is distinct from that arising from the wortmannin-inhibitable phosphatidylinositol 3-kinase. In addition, as exemplified by the rapamycin-resistant but mitogen- and wortmannin-sensitive p70 delta 29-46/ delta CT104 mutant, a further activating input, which probably involves site-specific phosphorylation in the segment between amino acids 46 to 421, is necessary.